Diagnosis of infectious diseases in immunocompromised hosts using metagenomic next generation sequencing-based diagnostics. (May 2022) - Casto, Amanda M.; Fredricks, David N.; Hill, Joshua A.
Abstract: The diagnosis of infectious diseases in immunocompromised hosts presents unique challenges for the clinician. Metagenomic next generation sequencing (mNGS) based diagnostics that identify microbial nucleic acids in clinical samples (mNGS for pathogen identification or mNGSpi) may be a useful tool in addressing some of these challenges. Studies of mNGSpi in immunocompromised hosts have demonstrated that these diagnostics are capable of identifying causative organisms in a subset of patients for whom conventional testing has been negative. While these studies provide proof of concept for mNGSpi utility, they have a number of limitations, which make it difficult to confidently assess test performance and clinical impact based on current data. Future studies will likely feature larger cohort sizes and controlled interventional study designs that assess the impact of mNGSpi on clinical endpoints. They will also likely include assessments of the clinical value of data generated by mNGS beyond pathogen identification.